Preparation of VO2/Al-O core-shell structure with enhanced weathering resistance for smart window. Issue 5 (1st April 2017) - Tong, Kun; Li, Rong; Zhu, Jingting; Yao, Heliang; Zhou, Huaijuan; Zeng, Xianzhe; Ji, Shidong; Jin, Ping
Abstract: VO2 /Al-O core-shell structure (V/AO) was synthesized by a facile method and its application for thermochromic film on smart window was investigated. Comparisons of thermochromic properties and stabilities in different environments between VO2 and annealed V/AO nanoparticles were made. As a result, VO2 nanoparticle was easily oxidized and lost thermochromic property. In contrast, with the protection provided by Al-O-based shell, the VO2 core remained stable at a high temperature (350 °C in air) and in H2 O2 solution. Especially, thermochromic films made by annealed V/AO nanoparticles almost kept thermochromic performance in damp heating environment (T=60 °C, RH=90%) for 20 days while VO2 films lost their thermochromic properties after 3 days. Besides, the degradation progress of VO2 and V/AO nanoparticles in damp heating environment was also explored. Results indicate that Al-O-based shell provides a good protection for the VO2 core originated from the compact structure of shell, which effectively prevents oxygen and water from eroding VO2 . In summary, the VO2 nanoparticles coated with Al-O-based shell exhibit a great potential in the application of smart window.